THE CORRELATION BETWEEN MUSIC AND ELEMENTARY SCHOOL DISCIPLINES - BADARNE, Belal; COCIERU, Natalia (Acta et Commentationes, Sciences of Education, 2019)
Music is inherent in the spoken language. Many young children appear to be naturally inclined to hum or to sing a tune. In this context, it is beneficial to build upon musical interests and enhance their literacy development simultaneously, by integrating music throughout curricular areas to develop comprehension skills, improve listening and oral language skill development, improve attention and memory, and enhance abstract thinking